Antifungal activity of extracts of weed biomass against Aspergillus flavus Link ex Fr., a causal agent of yellow mold of Groundnut - Deshmukh RS (International Journal of Life Sciences, 2017)
During the present studies, weeds found in different crop fields were screened to observe their antifungal activity against yellow mold causing fungi of groundnut i.e. Aspergillus flavus Link ex Fr. To study the antifungal mechanism of weed extract, poisoned food technique was followed. The efficacy of weed extracts was expressed as percent inhibition of mycelial growth over control. Among these weeds, leaf and stem extracts of Parthenium hysterophorus L. and Commelina benghalensis L. were found to be most effective against yellow mold causing fungi of groundnut i.e. Aspergillus flavus Link ex Fr.